2^(x-2)-11^(-10x)=0

Simple and best practice solution for 2^(x-2)-11^(-10x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2^(x-2)-11^(-10x)=0 equation:



2^(x-2)-11^(-10x)=0

You can always share this solution

See similar equations:

| 6w+7(w+3)=-31 | | -3=5(y-7)+3y | | 6(n+7)=2(21+3) | | 52=v+8v | | 9=10w-w | | 6x-2=5×-7-3× | | 5x-21=29 | | 2(m+13)=3m+3 | | 190=2l+2l+3 | | 27=1w-6w | | -8(v+4)+4v+6=8v+8 | | 9n-(7n+10)=6-(2n-5) | | -6(v+4)+3v+7=7v+11 | | 48=12d-7 | | 1+1a=9 | | 3w-6=5 | | 3(1x+1)+10=8-3x | | 13x-59=7x+25 | | -33=u/2 | | 3/4(56)=3/4x | | 5-3r=25 | | 7m^2-21m-70=0 | | 2^n-2=1000 | | 3z^+7z+20=0 | | -77+10x^2=-x^2 | | -19=-5u+3(u-3) | | 3,2x-3+1,8x=-3+5x | | 3x?45=?12 | | 4,5x+7=3+4,5x | | 4×x-2+3=19 | | -3+3x=15 |

Equations solver categories